REGULASI DIRI DALAM BELAJAR MAHASISWA DITINJAU DARI ORIENTASI TUJUAN DAN KELEKATAN TEMAN SEBAYA - Noni A Somad; M Nursalim Malay; Citra Wahyuni (Jurnal Ilmiah Psyche, 2022)
Self-regulated learning is the ability of an individual to play an active role in the learning process both in metacognition, motivation, anda behavior. One of the factors that influence self-regulated learning is goal orientation and peer attachment. The study aims to analyze the relationship between goal orientation and peer attachment with self-regulated in student learning. The implication in this study is how students pursue meaningful learning by using self-regulated in good learning. This type of research is quantitative. The method of data collection in this study was to use three types of psychological scales, namely self-regulates learning, goal orientation, and peer attachment in the from of a questionnaire distributed throught google from media. The subjects in this study were 480 active students of UIN Raden Intan Lampung. The sampling technique using accidental sampling. Validity in this study using content validity and reliability using cronbach’s alpha. In this study using partial correlation and multiple regression data analysis techniques wuth the JASP software version 0.16.3.0. The results in this study obtained a value of R = 0.843 with a value of F = 165.083 (p<0.01) it shows that there is a significant positive relationship between goal orientation and peer attachment with self-regulated learning in university students. Goal orientation variables and peer attachment have an effect of 71.1% on self-regulated learning in university sudents..